Are the small companies is the best investment? in Malaysia perspective / Mohd Shahril Zainal Abidin (Faculty of Business and Management, 2007)
This paper study whether the small companies are the better investment medium compared to large companies by looking at the performance of the companies. It also study whether the small companies is outperformed the market This study used 70 companies that listed in main board of Bursa Malaysia The companies that will be chose is based on their asset equity. To measure the performance, the study used Sharpe index, Jentson's alpha performance index and Treynors performance index. In addition, T tests are using to determine the performance of the companies. Both small and large companies are underperformed compared to the market. In addition the result shows that small companies is not the best medium investment compared to the large companies.